"Hitting the nail on the head". Issue 1 (20th December 2006) - Fries, A; Higginson, I
Abstract : Subungual malignant melanoma is a rare form of malignancy that can present at an advanced stage. We describe a case that was diagnosed after a presentation to the emergency department for a traumatic injury of the affected area. Initial presentations of malignant disease and its complications form a relatively low proportion of the caseload of emergency doctors. In this case, a patient presented after a minor injury that had failed to recover; subsequent investigation of this injury led to the diagnosis of subungual malignant melanoma in an otherwise asymptomatic patient. This is a rare case which presented in an atypical fashion, with a confounding history of minor trauma. It is presented to highlight the differential diagnosis of destructive bone lesions.